Investigation of Mathematical Self-Efficacy Perceptions of Secondary School Science Teacher Teachers - Geçer, Kelimetullah (Fırat University, 2018)
The purpose of this study is to examine some of the variables of middle school science teacher candidates' selfefficacy beliefs towards teaching mathematics. In order to determine the self-efficacy beliefs of teacher candidates for mathematics teaching as a data collection tool in this direction, Hacıömeroğlu and Taşkın (2010) used Enochs et al. (2000) adapted the Turkish version of the Mathematics Teaching Proficiency Beliefs Scale and developed the personal information form developed by the researcher in order to gather necessary information about teacher candidates. The sample of the study is composed of 135 teacher candidates who are studying in the Department of Science Teacher Education of the Van Yüzüncü Yıl University Faculty of Education. According to the results of the analysis, it has been determined that prospective teachers' self-efficacy beliefs about mathematics teaching are generally high. Moreover, it was determined that the science teachers’ candidates did not show a statistically significant difference in mathematics teaching self-efficacy beliefs according to gender, class level and graduated high school type variables.

Bu çalışmanın amacı, ilköğretim fen bilgisi öğretmeni adaylarının matematik öğretimine yönelik öz-yeterlik inançlarının bazı değişkenlere göre incelemektir. Bu amaç doğrultusunda veri toplama aracı olarak, öğretmen adaylarının matematik öğretimine yönelik öz-yeterlik inançlarını belirlemek için Hacıömeroğlu ve Taşkın (2010) tarafından Enochs ve diğ. (2000)’ nin geliştirmiş oldukları Matematik Öğretimi Yeterlik İnanç Ölçeğinin Türkçe’ ye uyarlanmış hali ve öğretmen adayları hakkında gerekli bilgileri toplamak amacıyla araştırmacı tarafından geliştirilen kişisel bilgi formu kullanılmıştır. Çalışmanın örneklemini Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Fen bilgisi öğretmenliği bölümünde öğrenim görmekte olan toplam 135 öğretmen adayı oluşturmaktadır. Analiz sonuçlarına göre, öğretmen adaylarının matematik öğretimine yönelik öz-yeterlik inançları genel olarak yüksek düzeyde olduğu tespit edilmiştir. Ayrıca, öğretmen adaylarının matematik öğretimi öz-yeterlik inançları cinsiyet, sınıf düzeyi ve mezun olunan lise türü değişkenlerine göre istatistiksel olarak anlamlı bir farklılık göstermediği belirlenmiştir.
İlköğretimde Fen Bilgisi Öğretmeni Adaylarının Matematik Öğretimine Yönelik Öz Yeterlik İnançlarının İncelenmesi